1999
DOI: 10.1007/bf02496010
|View full text |Cite
|
Sign up to set email alerts
|

Radical functionalization of [60]fullerene and its derivatives initiated by the C(CF3)2C6H4F radical

Abstract: It was found that the 2-(p-fluorophenyl)hexafluoroisopropyl radical produced by thermal dissociation of the Polishchuk dimer [C(CF3)2C6H4F]2 can withdraw, under mild conditions, the H atom from the methyl group of toluene and mesitylene to form the corresponding radicals, whose addition to [60]fullerene occurs more selectively than in the case of photochemical production of these radicals. Dynamics of the step-by-step multiaddition of the radicals to C60 was studied by ESR. It was found that the addition of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Multiple radical addition to C 60 is another important characteristic in the chemistry of fullerenes. Pioneering studies in this field have shown that prolonged irradiation of C 60 solutions in the presence of excess radical precursors leads to multiple radical additions, as confirmed by line broadening in the ESR spectra and by mass spectroscopy. ,,, For example, it has been shown that photochemically generated benzyl radicals react with C 60 , producing radical and nonradical adducts R n C 60 (R = C 6 H 5 CH 2 ) with n ranging from 1 to at least 15 . Radical adducts with n = 3 and 5 have been identified by ESR spectroscopy as the allylic radical R 3 C 60 • ( 3 ) and cyclopentadienyl radical R 5 C 60 • ( 5 ), respectively, whereas the unpaired electrons were found to be highly localized on the C 60 surface (Scheme ).…”
Section: Addition Of C-centered Radicals To Fullerenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple radical addition to C 60 is another important characteristic in the chemistry of fullerenes. Pioneering studies in this field have shown that prolonged irradiation of C 60 solutions in the presence of excess radical precursors leads to multiple radical additions, as confirmed by line broadening in the ESR spectra and by mass spectroscopy. ,,, For example, it has been shown that photochemically generated benzyl radicals react with C 60 , producing radical and nonradical adducts R n C 60 (R = C 6 H 5 CH 2 ) with n ranging from 1 to at least 15 . Radical adducts with n = 3 and 5 have been identified by ESR spectroscopy as the allylic radical R 3 C 60 • ( 3 ) and cyclopentadienyl radical R 5 C 60 • ( 5 ), respectively, whereas the unpaired electrons were found to be highly localized on the C 60 surface (Scheme ).…”
Section: Addition Of C-centered Radicals To Fullerenesmentioning
confidence: 99%
“…Employment of thermal instead of photochemical methods for radical generation has allowed for more selective addition of benzyl radicals to C 60 . In particular, Tumanskii and co-workers have shown that the 2-( p -fluorophenyl)hexafluoroisopropyl radical, produced by thermal dissociation of the dimer [(FC 6 H 4 )C(CF 3 ) 2 ] 2 , can abstract a hydrogen atom from the methyl group of toluene and mesitylene to form the corresponding radicals which then add selectively to fullerene C 60 . Thus, it was found that addition of benzyl radicals affords adducts containing from 3 to 5 benzyl groups, whereas in the case of the 3,5-dimethylphenylmethyl radicals, the fifth radical does not add, probably due to the steric hindrance caused by its large size compared to that of the benzyl radical …”
Section: Addition Of C-centered Radicals To Fullerenesmentioning
confidence: 99%
“…A stepwise addition of benzyl radicals could be observed by using the dimer [F(C 6 H 4 )C(CF 3 ) 2 ] 2 as a radical precursor [9,49]. Every 10 to 20 min, one more radical is added to C 60 and these subsequent additions can be studied in the ESR spectrum.…”
Section: Esr Investigations Of Radical Additionsmentioning
confidence: 99%
“…Elimination of a hydrogen atom from C 60 H 36 under mild conditions can also be carried out by treatment with the 2-(p-fluorophenyl)hexafluoroisopropyl radical. 123 Heating (353 K) of hydrofullerenes C 60 H x (x = 6 ± 18) with Hg[N(SiMe 3 ) 2 ] 2 , Ti[N(SiMe 3 ) 2 ](NEt 2 ) 3 and other metal complexes also results in elimination of a hydrogen atom from C 60 H x and formation of fullerene-containing oligomers, e.g.,…”
Section: The Reactivities Of Hydrofullerenesmentioning
confidence: 99%